Analisis Penerapan Ekoliterasi Pada Anak Usia Dini di Lingkungan Alambarajo Kota Jambi - Salsabila, Shilfa Sukma; Siregar, Masyunita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to apply ecoliteracy to early childhood in the Alambarajo environment of Jambi City. The research method in this study uses qualitative descriptive which aims to describe the ecoliteracy abilities of children in their environment, namely in Alambarajo District, Jl.Bersama, Jambi City. The application of ecoliteracy in the Alambarajo environment has been running well, as seen from the Head (knowledge) and Heart (Attitude) in early childhood in the Alambarajo environment of Jambi City has developed well, this knowledge can develop children's thinking skills contextually in the form of experiences in everyday life in the environment which aims to develop children's thinking skills in solving problems efficiently in their environment.